2004
DOI: 10.1002/eji.200324511
|View full text |Cite
|
Sign up to set email alerts
|

The Toll‐like receptor ligand MALP‐2 stimulates dendritic cell maturation and modulates proteasome composition and activity

Abstract: A 2-kDa synthetic derivative of the macrophage-activating lipopeptide (MALP-2) from Mycoplasma fermentans is a potent inducer of monocytes/macrophages and improves the immunogenicity of antigens co-administered by systemic and mucosal routes. Dendritic cells (DC) are the most potent antigen-presenting cells, which are able to prime naive T cells in vivo. To elucidate the underlying mechanisms of MALP-2 adjuvanticity, we analyzed its activity on bone marrow-derived murine DC. In vitro stimulation of immature mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 43 publications
(38 reference statements)
2
45
1
Order By: Relevance
“…Our experiments with cytokine receptor knockout (KO) mice demonstrate that lack of TNF-␣ signaling does not influence the induction of I-proteasome during L. monocytogenes infection. Furthermore, it has been shown that stimulation of TLRs leads to induction of immunosubunits in dendritic cells (35) and is involved in the control of L. monocytogenes infection (36). However, our studies suggest that stimulation of TLR by bacterial components cannot induce I-proteasomes in nonlymphoid tissues.…”
Section: Discussioncontrasting
confidence: 54%
“…Our experiments with cytokine receptor knockout (KO) mice demonstrate that lack of TNF-␣ signaling does not influence the induction of I-proteasome during L. monocytogenes infection. Furthermore, it has been shown that stimulation of TLRs leads to induction of immunosubunits in dendritic cells (35) and is involved in the control of L. monocytogenes infection (36). However, our studies suggest that stimulation of TLR by bacterial components cannot induce I-proteasomes in nonlymphoid tissues.…”
Section: Discussioncontrasting
confidence: 54%
“…It is likely that this high immunogenicity arises from the covalently linked lipid moiety, which acts as a danger signal (1-3) by stimulating the innate immune system via the pattern recognition receptor TLR 2/6. This capacity is retained by both natural MALP-2 and synthetic derivatives, which are able to activate different cellular subtypes (12,19,23). However, the role played by these lipopeptides during natural infections has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that MALP-2 is an agonist of the TLR2/6 heterodimer, leading to a Toll-IL-1R domain-containing adapter protein and MyD88-dependent activation of NF-B in macrophages (9 -11). Consequently, incubation of macrophages and dendritic cells with MALP-2 results in the secretion of proinflammatory cytokines and enhances the capacity of dendritic cells to present Ags to T cells (12). Since the adjuvanticity of MALP-2 is characterized by strong humoral responses and B cells express TLR2/6 (13), B cells could be a potential target for MALP-2-mediated activation in vivo.…”
mentioning
confidence: 99%
“…95 These results have been independently confirmed in BALB/c mice using MALP-2, and extended to show that the lipopeptide also upregulates immunoproteasome (LMP2, LMP7 and MECL1) activity in a dose-dependent manner, suggesting that lipopeptides may indirectly enhance MHC Class I-restricted responses by accelerated antigen processing and peptide presentation. 96 Importantly, the effects of lipopeptides on APC maturation and antigen presentation have also been demonstrated in human DCs. 97 MALP-2 directly stimulates murine B lymphocytes without accessory APC help in a TLR2-and dose-dependent fashion.…”
Section: Tlr1/tlr2/tlr6 Agonistic Bacterial Lipoteichoic Acid and Lipmentioning
confidence: 99%